Listeria monocytogenes Impact on Mature or Old Pseudomonas fluorescens Biofilms During Growth at 4 and 20°C - Puga, Carmen H.; Orgaz, Belen; SanJose, Carmen (Frontiers in Microbiology, 2016)
Changes in spatial organization, as observed by confocal laser scanning microscopy (CLSM), viable cell content, biovolume and substratum surface coverage of the biofilms formed on glass by Pseudomonas fluorescens resulting from co-culture with Listeria monocytogenes, were examined. Two strains of L. monocytogenes, two culture temperatures and two biofilm developmental stages were investigated. Both L. monocytogenes strains, a persistently sampled isolate (collected repeatedly along 3 years from a meat factory) and Scott A, induced shrinkage in matrix volume, both at 20ºC and 4ºC, in mature or old biofilms, without loss of P. fluorescens cell count per surface unit. The nearly homogeneous pattern of surface coverage shown by mono-species P. fluorescens biofilms, turned into more irregular layouts in co-culture with L. monocytogenes. The upper layer of both mono and dual-species biofilms turned to predominantly consist of matrix, with plenty of viable cells underneath, in old biofilms cultured at 20ºC, but not in those grown at 4ºC. Between 15 and 56% of the substratum area was covered by biofilm, the extent depending on temperature, time and L. monocytogenes strain. Real biofilms in food-related surfaces may thus be very heterogeneous regarding their superficial components, i.e. those more accessible to disinfectants. It is therefore a hygienic challenge to choose an adequate agent to disrupt them.